Synthesis of Non‐Symmetric Ruthenium(II) POCOP Pincer Complexes and Their Bimetallic Derivatives by π‐Coordination of Arenophile Fragments. Issue 28 (13th July 2020) - Roque‐Ramires, Manuel A.; Shen, Longzhu; Le Lagadec, Ronan
Abstract : A series of neutral 16‐electron square pyramidal ruthenium(II) complexes of the general formula [Ru(POCOP)(X)(CO)] (X = Cl, H) have readily been obtained in good yields from [RuCl2 (COD)] n and different POCOP pincer ligands based on the naphthoresorcinate backbone. The molecular structure of two of the compounds was unequivocally determined by single‐crystal X‐ray diffraction, showing different stereochemistries upon the coordination of chloride or hydride ligand. The observed discrepancies are explained by DFT calculations. The regiospecific η 6 ‐coordination of a second 12‐electron organometallic fragment on the exo aromatic ring of the POCOP pincer ligand was achieved under mild conditions, and the corresponding [(MLn )Ru(POCOP)(X)(CO)]PF6 (MLn = [RuCp] +, [RuCp*] + and [FeCp*] + ) bimetallic sandwich‐like species were obtained as air‐stable solids. Abstract : Square pyramidal ruthenium(II) complexes bearing non‐symmetric POCOP pincer ligands were readily prepared. The corresponding homo‐ and heterobimetallic derivatives were obtained by regiospecific coordination of an arenophile organometallic fragment to the exo ring of the pincer moiety.